Protective compromise of great omentum in an asymptomatic uterine rupture in a bitch : a case report (2010)
ABSTRACT: The great omentum plays an important role in protecting the peritoneal cavity from bacteria and contaminating material and providing the peritoneum with leukocytes from the omental milky spots (OMS). However, there are no reports on the existence of OMS in dogs. In this report an unusual case of asymptomatic uterine rupture (UR) is described in a 16 month old pointer bitch that was admitted at the CES University Veterinary Clinic in Medellin (Colombia) for elective neutering. In the abdominal surgical plane, the great omentum was found sequestering abundant macerated fetal debris and uterine content released near the ruptured uterine wall. A severe congestive and brown-like appearance of peritoneum suggesting a protective inflammatory process was observed. All uterine contents, uterus and compromised great omentum were completely removed. The dog recovered satisfactorily with no clinical complications after a long term postsurgical period. Additionally we discuss the existence of OMS in the canine omentum.